Deal Cash: Digital Platform Trending Pemasaran Hasil Pertanian dalam Meningkatkan Perekonomian di Era 4.0 - Abul Mawahib. R; Sri Wahyuni; Nurfadillah Nurfadillah (EXERO : Journal of Research in Business and Economics, 2021)
Advances in technology have provided many benefits and conveniences as well as a new way of doing activities for human life. The development of technology known as the industrial revolution 4.0 brings many changes with all the consequences that require one to master in its operation, including competing in the digital economy. Indonesia as an archipelagic country has biological resources that make it have high economic potential. The agricultural sector plays an important role in the Indonesian economy. Agriculture is an activity of managing biological resources to achieve superior agricultural commodities in each sector. Indonesia's agricultural sector still has many problems such as capital and marketing. This research examines Deal Cash: Digital Marketing Platform for Independent Agricultural Products in Improving the Economy in Era 4.0. This research uses a literature study approach through qualitative descriptive research. The purpose of writing this scientific paper is to describe the concept and benefits of the Deal Cash application as a form of marketing in improving the economy in the industrial revolution 4.0 era. Deal Cash is a research innovation in the form of a fintech-based digital platform as a solution for farmers from problems faced such as capital and marketing. Products that can be marketed include food crops, plantation, fishery and livestock products. Deal Cash has four main services, namely sales, purchase, distribution and capital loan services. Deal Cash aims to make it easier for related parties to carry out marketing, distribution or ordering transactions to meet their needs.